Pengaruh Peer Education Terhadap Pengetahuan Dan Sikap Remaja Putri Yang Mengalami Anemia - Ulfa Badri; Defrin Defrin; Afdal Afdal; Firdawati Firdawati; Zelly Dia Rofinda; Gestina Aliska (Universitas Pahlawan Tuanku Tambusai, 2026)
Iron deficiency anemia is a common nutritional problem among adolescent girls in Indonesia. According to the World Health Organization (WHO), the prevalence of anemia among adolescents worldwide was 32.5% in 2020. UNICEF data (2021) reported that in Indonesia, the highest prevalence of anemia was found among adolescents aged 13–15 years, at 22.7%. Providing health education about anemia and balanced nutrition is necessary to minimize the incidence of anemia among adolescent girls. This study aims to determine the effect of peer education on changes in knowledge and attitudes among adolescent girls with anemia at MTsN 6 Kota Padang. The study, using a pre-experimental design, was conducted at MTsN 6 Kota Padang from February to August 2025. The sample consisted of 52 adolescent girls with anemia, selected using consecutive sampling. Data were analyzed using univariate and bivariate methods, with the Wilcoxon test (p≤0.05). The results showed that 83% of the female students experienced an increase in knowledge (p=0.001), while 69% experienced an increase in positive attitudes (p=0.001). Statistically, there was a significant difference in knowledge and attitudes among anemic female adolescents after receiving peer education.